Analysis of the state of training of specialists in the health technology assessment in the world - V. N. Nаzаrkinа (The State Expert Center of the Ministry of Health of Ukraine, 2020)
In order to support the development of a Health Technology Assessment (НTA) in Ukraine, it is necessary to create a professional environment. The organization of training specialists in НTA is relevant for all countries of the world, including Ukraine. The aim of the work is to summarize the experience of training specialists of health technologies assessment and related branches of knowledge in different countries of the world, to analyze the curricula and courses for the development of this educational area in Ukraine. The subject of the study were scientific publications of domestic and foreign scientists, official sites of educational institutions, national agencies on the НTA and international organizations, as well as educational portals and training centers. The studies were conducted using methods of analysis, systematization and generalization. The structure and content of different training programs for health technologies assessment and related branches of knowledge used to meet the information needs of various target audiences (HTA experts, policy makers, healthcare managers, medical and pharmaceutical workers) were analyzed. The most common forms of training are courses, trainings and seminars, which are considered as a means of professional development. Academic programs (master degree, master of science, PhD) in Health Technology Assessment have 13 countries in Europe. To increase awareness of Health Technology Assessment distance learning is widely implemented within Massive Open Online Courses (MOOC). Flexible adaptation to the needs of students allows to obtain, as a result of training, a certificate/diploma of a graduate, a master's degree/master of science or Ph.D. Online courses are also considered as refresher training, non-assessment training for self-improvement and professional development audit. Taking into account the foreign experience of training specialists in НTA, the qualification characteristic of a specialist in health technology assessment and the author's educational program have been developed. For the first time in Ukraine in 2019 at the National University of Pharmacy, training of specialists on the evaluation of health technologies was started. The educational direction of НTA expert training requires development and support from the state and professional institutions.